2008
DOI: 10.2106/jbjs.h.00081
|View full text |Cite
|
Sign up to set email alerts
|

Corrective Osteotomies in Spine Surgery

Abstract: Spinal deformities can result in increasing thoracic kyphosis or loss of lumbar lordosis, leading to imbalance in the sagittal plane. Such deformities can be functionally and psychologically debilitating. The Smith-Petersen osteotomy can achieve approximately 10 degrees of correction in the sagittal plane at each spinal level at which it is performed. This osteotomy is beneficial for patients who have a degenerative imbalance in the sagittal plane. The pedicle subtraction osteotomy can achieve approximately 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(89 citation statements)
references
References 26 publications
0
88
0
1
Order By: Relevance
“…30 Subsequently, these techniques have been adapted to treat fixed sagittal imbalance with excellent results. [6][7][8]15 These publications have elucidated the power of the PSO and SPO to affect regional and global parameters and have provided valuable guidance in operative planning. 6,15 The anticipated rate of lumbar lordosis and sagittal vertebral axis correction for the PSO is 30°-40° and 5.5-13.5 cm per level, respectively.…”
Section: Traditional Approach Versus Mi-lif With Acrmentioning
confidence: 99%
“…30 Subsequently, these techniques have been adapted to treat fixed sagittal imbalance with excellent results. [6][7][8]15 These publications have elucidated the power of the PSO and SPO to affect regional and global parameters and have provided valuable guidance in operative planning. 6,15 The anticipated rate of lumbar lordosis and sagittal vertebral axis correction for the PSO is 30°-40° and 5.5-13.5 cm per level, respectively.…”
Section: Traditional Approach Versus Mi-lif With Acrmentioning
confidence: 99%
“…Despite variations in techniques, 3COs are effective procedures that allow for the correction of spinal deformity and the restoration of global alignment. 2,4,9,10,26,27 While 3CO procedures are powerful tools in the surgeon's armamentarium for the treatment of spinal deformity, the complexity of these procedures can result in major complications. Analysis of the Scoliosis Research Society morbidity and mortality database showed that patients who underwent osteotomies had higher rates of complications than those who underwent other surgical approaches, and more aggressive osteotomies were associated with higher complication rates.…”
mentioning
confidence: 99%
“…Sagittal balance restoration is more important as it facilitates decreased energy requirements on walking, improving cosmesis and patient satisfaction. It also limits pain, fatigue and complications associated with new or untreated deformities (5) There are several recognized techniques which describe correction of a fixed sagittal imbalance (6)(7)(8). These include posterior only or anterior/posterior combined approaches, osteotomies such as the Smith-Peterson osteotomy (SPO), …”
Section: Discussionmentioning
confidence: 99%